The Efficiency of Micro Steel Fiber (MSF) in Concrete Performance by Using Ultrasonic Pulse Velocity (UPV) - Hanafi, Farah Hanim; Shahiron Shahidan; Suchitra Ramasamy; Nurul Izzati Raihan Ramzi Hannan (Recent Trends in Civil Engineering and Built Environment, 2021)
The plain concrete is low tensile strength and strain capacity, that is, concrete is a brittle material. Micro steel fiber (MSF) is one of the proven materials that can significantly change the behavior of different types of concrete mixtures from brittle to more ductile ones. It also has excellent in improvement of compressive strength. Therefore, this research aims to determine the performance of MSF concrete in undamaged and damaged state. Then, the concrete samples were tested using the Ultrasonic Pulse Velocity (UPV) method. The UPV method is an effective non-destructive testing (NDT) method for ensuring quality control of concrete materials as it helps detect damages in structural components. Two ways were used to place in tranducers to the specimens in this research which are direct and semi-direct method. The chosen percentages of fibre used were 0%, 0.5%, 0.75%, 1.0% and 1.25%. The specimens underwent the UPV test and the compressive strength test on day 7 and day 28. The increased of micro steel fiber content in concrete mixes was effected the pulse-velocity value were increased. Direct method was found as the best method of the UPV testing. So, from the direct method of the UPV test, the optimum percentage suggested according to the results is 0.75% of MSF as it fulfilled the relationship between compressive strength and UPV compared to the normal concrete.